Analisis trend pengundian berdasarkan kaum di kawasan Bukit Gantang, Perak - Junaidi Awang Besar,; Mohd FuadMat Jali,; Abdul Halim Sidek,; Yahaya Ibrahim,; Noor Aziah Hj. Mohd Awal,; Khaidzir Hj. Ismail, (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2010)
The Parliamentary by-election of Bukit Gantang was held on the 7th April 2009 after the death of incumbent, Roslan Shaharum, of PAS. This election is said to be an indicator of public referendum whether to accept or not the establishment of a new government under the BN State government. The result of the study shows that almost 100 percent of the Malays, Chinese and Indians respondents choose television as their main source of political information. In terms of candidate selection criteria, 72.1 percent of Chinese respondents, 67.9 per cent Malays and 47.9 per cent Indians choose people-friendly candidate. 78.7 percent of the Malays, 81.6 per cent Chinese and 48.9 per cent of Indian respondents agree that they will not allow their elected representatives to resign and join other party. Concerns about the constitutional crisis of Perak state, the Malays were more likely to show support for the Royal Institution but not from the Chinese and Indian respondents. Referring to the expected victory, 27.0 percent of Malay respondents, 34.2 per cent Chinese and 57.3 per cent Indians said PAS will win the election compared to 45.5 percent of Malay respondents, 35.5 per cent Chinese and 20.8 per cent Indians predicted BN will win the by-election of Bukit Gantang. The three ethnic groups agreed that the Prime Minister of Malaysia, Dato’ Sri Mohd. Najib Tun Haji Abdul Razak will lead the development of the country more innovative and progressive